(untitled) (Research, Society and Development, 2021)
Due to the predominantly tropical climate, Brazil has a high incidence of arboviruses. Among them stand out those transmitted by Aedes aegypti, the main vector for dengue and Zika. However, given the pandemic caused by Covid-19, the situation in Brazil may have changed regarding the effectiveness of notification and control of these pathologies. In order to verify such a scenario, an ecological, descriptive study was carried out, from 2019 to 2020. The Notifiable Diseases Information System (SINAN) and the Mortality Information System (SIM) are made available by the Department of Informatics of the Unified Health System (DATASUS) through the Health Information Platform (TABNET). The results showed that in the state of Minas Gerias, in 2020 only 8,7% (n=85,356) cases of dengue and 34% (n=1,350) of Zika were confirmed, in 2019 this number reached (n=478,898) cases of dengue and 45,3% (n=3,228) in cases of Zika, i.e., there was a reduction of 82.17% in dengue notification in 2020 and 58.17% in cases of Zika Virus. These data suggest that efforts to contain the emerging entity Covid-19 may make it impossible to notify and effectively diagnose the aforementioned pathologies. Similar symptoms among diseases may also contribute to such a scenario. In addition, it is believed that the fear related to Covid-19 infection has made it difficult to report and delay the diagnosis. It is concluded that there is a need for the development of policies that encourage notification, control of the pathogen, population education and health measures due to early diagnosis and monitoring of necessary and predictive.